Analysis of the Role and Obstacles of Teachers in Building Students’ Independent Character - Firmansyah, Wilis; Rahmalia, Siti Maulida (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study aims to analyze the role and obstacles faced by teachers in developing students’ independent character, particularly at the elementary school level. Character education, including the value of independence, is an essential part of the learning process that must be instilled from an early age to shape a responsible and resilient generation. Using a descriptive qualitative approach, this study combined literature review and direct interviews with Mrs. Ipah Syaripah, the second-grade homeroom teacher at MI Al Khoeriyah 01, as the primary data source. The results indicate that teachers play a crucial role as educators, facilitators, and role models in developing students’ independent character. Teachers guide students through daily classroom responsibilities, assign independent projects, and create a learning environment that encourages active participation. However, in practice, teachers also face several obstacles, such as a lack of motivation and self-confidence in students, differences in individual readiness levels, and limited learning time at school. To overcome these challenges, teachers strive to provide motivation, set realistic learning targets, and establish good cooperation with parents so that the value of independence can be developed sustainably.